Content management systems as a cornerstone in the deployment of semantic web - Pastor-Sánchez, Juan-Antonio (Anuario ThinkEPI, 2012)
The semantic web has enough critical mass to expand its technological scope to content management systems (cms). Currently, an increase in the application of interoperable standards to publish large datasets is detected. Rdf, owl and sparql are replacing traditional developments based on relational database management systems for management and storage of information. Cms are beginning to use these technologies to publish content with semantic web formats, and to define mappings with elements of rdf vocabularies. In this regard, Cms also incorporate features to add semantic information into the xhtml code using rdfa and applying sparql to query data or incorporate external data.